Clinical diagnosis of seasonal influenza by physicians: a retrospective observational study - Hiroyuki Kato; Tadashi Kobayashi; Hiroki Maita; Takashi Akimoto; Fumihiko Matsuoka; Shigeki Funakoshi; Hiroshi Osawa (BMJ Open)
Objective To elucidate the diagnostic accuracy of pretest probability of influenza (%) by physicians and the factors affecting the clinical diagnosis.Design Retrospective, single-centre observational study.Setting A community primary care clinic in Japan.Participants The participants were recruited from a database of studies conducted during the influenza season from December 2017 to April 2019.Primary outcome measure Sensitivity and specificity of the physician’s clinical diagnosis of influenza recorded in the medical record as pretest probability.Results A total of 335 patients (median age, 31 years; male, 66.6%) were analysed in this study. The area under the curve (AUC) of the physician’s pretest probability was 0.77. At a cut-off value of 30%, the sensitivity and negative likelihood ratio were 92.0% (95% CI 86.7 to 95.7) and 0.19 (95% CI 0.11 to 0.33), respectively. At a cut-off value of 80%, the specificity and positive likelihood ratio were 90.8% (95% CI 85.4 to 94.6) and 4.01 (95% CI 2.41 to 6.66), respectively. The AUCs of patients who had and had not taken any medications before visiting the clinic were 0.77 (95% CI 0.69 to 0.85) and 0.78 (95% CI 0.71 to 0.84), respectively. The AUCs of patients with type A and B influenza were 0.78 (95% CI 0.72 to 0.84) and 0.76 (95% CI 0.70 to 0.82), respectively. The AUCs of vaccinated and unvaccinated patients were 0.80 (95% CI 0.72 to 0.88) and 0.76 (95% CI 0.63 to 0.89), respectively. The AUC for patients less than 12 hours after onset was 0.69 (95% CI 0.51 to 0.88), and that for patients aged younger than 6 years was 0.69 (95% CI 0.49 to 0.88).Conclusions The physician’s pretest probability of influenza (%) may be useful for both definitive and exclusionary diagnoses within the limits of our study.